Beta-xilosidases induzidas por resíduos agroindustriais: análise da regulaçãogênica em caulobacter crescentus e produçãoenzimática por thermomyces lanuginosus - Corrêa, Juliana Moço (2014)
PAPER 1 Depletion of the xynB2 gene upregulates β-Xylosidase expression in C. crescentus. Caulobacter crescentus is able to express several enzymes involved in the utilization of lignocellulosic biomasses. Five genes, xynB1-5, that encode β-xylosidases are present in the genome of this bacterium. In this study, the xynB2 gene, which encodes - xylosidase II (CCNA_02442), was cloned under the control of the PxylX promoter to generate the O-xynB2 strain, which overexpresses the enzyme in the presence of xylose. In addition, a null mutant strain, -xynB2, was created by two homologous recombination events where the chromosomal xynB2 gene was replaced by a copy that was disrupted by the spectinomycin-resistant cassette. It was demonstrated that C. crescentus cells lacking -xylosidase II up-regulates the xynB genes inducing β- xylosidase activity. Transcriptional analysis revealed that xynB1 (RT-PCR analysis) and xynB2 (lacZ transcription fusion) gene expression was induced in the -xynB2 cells, and high -xylosidase activity was observed in the presence of different agroindustrial residues in the null mutant strain, a characteristic that can be explored and applied in biotechnological processes. In contrast, overexpression of the xynB2 gene caused down-regulation of the expression and activity of the -xylosidase. For example, the β-xylosidase activity that was obtained in the presence of sugar cane bagasse was 7-fold and 16-fold higher than the activity measured in the C. crescentus parental and O-xynB2 cells, respectively. Our results suggest that -xylosidase II may have a role in controlling the expression of the xynB1 and xynB2 genes in C.crescentus. PAPER 2 - OPTIMIZATION OF THE PRODUCTION β-XYLOSIDASE: A NEW Thermomyces lanuginosus ISOLATED FROM ATLANTIC FOREST BIOME. The successful production of enzymes for the deconstruction of plant biomass depends not only on the isolation and identification of new microorganism producers of hemicellulases, but also on the implementation and improvement of experimental strategies that lead to maximal induction of enzymatic activities. In this work, a new strain of Thermomyces lanuginosus (T. lanuginosus) was isolated from the Atlantic Forest biome in Brazil, and its β-xylosidase activity in response to agro-industrial residues was tested. Using the (CCRD) statistical approach as a strategy for optimization, the induction of β-xylosidase activity was evaluated in residual corn straw, which was used as a carbon source, and improved so that the optimum condition achieved high β-xylosidase activity (1,003 U ml -1; specific activity = 1.683 U mg-1) with 214 U ml -1. The optimal conditions for the crude enzyme extract were pH 5.5 and 60° C showing better thermostability at 55° C. The saccharification ability of β-xylosidase in the presence of hemicellulose obtained from corn straw and xylan from beechwood substrates showed a xylo-oligosaccharide to xylose conversion yield of 80 and 50%, respectively, at 50° C. These data suggest that β-xylosidase from T. lanuginosus isolated from the Atlantic Forest can be used for the saccharification of hemicellulose derived from corn straw, an abundant residue in the American continents, thus providing an interesting alternative for future tests for energy production that relies on the conversion of plant biomass.